Conceptually meeting expectations of Generation Y by building personalised-customised hybrid bundles to target action sports consumers - Parris, Denise Linda (My University, 2014)
This paper conceptually explores how bundling could lead to greater revenue and brand loyalty in the action sports industry by meeting the expectations of Generation Y. The author defines personalised-customised hybrid bundles and proposes using these bundles to target Generation Y action sports consumers. Generation Y grew up in an even more media-saturated and brand-conscious world then their parents. They use brands for self-expression to define what is 'cool' and seek counter cultures such as action sports. They expect a virtual dialogue with companies and comparison shop quickly. The author explores how bricks-and-clicks retailers can sell distinct products with different costs in a bundle through utilising multi-channel customer management (MCM) in combination with customer's self-selection. A conceptual model is developed explaining how action sports capture Generation Y, and a second model demonstrates how MCM combined with customer self-selection can be used to create personalised-customised hybrid bundles.
Keywords: Revenue; Action Sports; Generation Y; Multi-channel customer management; Branding; Personalised-customised hybrid bundles